First record of Calycina Blair, 1922 (Coleoptera, Mordellidae) in the Russian Far East with description of a new species - Ruzzier, Enrico; Kovalev, Alexey V. (Zootaxa, 2016)
The genus Calycina Blair, 1922 (Mordellinae, Mordellini) is one of the most fascinating and enigmatic genera of Mordellidae. The genus exhibits a pantropical distribution: one species with two subspecies in South America (Horák 1999; Leblanc 2013), one species in Africa (Horák 1999), three species in Southeast Asia (Horák 1999) and two species in the Papuan Region (Horák 1999; Ruzzier 2013). All species are known from only a few specimens, almost exclusively females, and appear to be generally very rare. Only Calycina major Nomura, 1967 and Calycina nigroapicalis Nomura, 1967 reach the Palearctic Region (Horák 2008; Ruzzier 2013) and no other species have been recorded from higher latitudes. The opportunity to study specimens from the Primorye region (Russian Far East) allowed the authors to identify a new species that is described below.